PERAN GURU PPKn DALAM MENGEMBANGKAN SIKAP NASIONALISME SISWA DI KELAS VII-C SMP SWASTA KRISTEN BNKP TELUK DALAM - Soni Halawa (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
The attitude of nationalism must be possessed by all citizens and can be instilled in children both at home and at school. So the problem of nationalist attitudes has become a collective task, namely from family, society, government. The research objectives are 1) To determine the role of PPKn teachers in developing students' nationalistic attitudes in class VII-C of BNKP Teluk Dalam Christian Private Middle School. 2) To determine the nationalist attitudes of students in class VII-C of BNKP Teluk Dalam Christian Private Middle School. This research uses qualitative research. The research subjects were students in class VII-C. Research results 1) The role of PPKn teachers in developing nationalist values ​​in class VII-C students is by transferring nationalist values ​​which aim to become students who are honest, disciplined, respect teachers or older people, dare to express opinions, love the homeland, respect religious, ethnic and cultural diversity, and provide good role models for students. 2) The attitudes of nationalism that exist in class VII-C students include attitudes of love for the country, discipline, respect for teachers, courage and honesty. Researchers provide several suggestions, namely 1) Students should study harder and always be disciplined at school and must always practice nationalist values ​​wherever they are. 2) PPKn teachers should create a school atmosphere that better reflects nationalist values, such as holding displays of photos of national heroes in every school environment, getting students used to singing and requiring students to memorize national songs and making written displays that have meaning. Struggle.